AB0861 Relationship between disease duration and treatment response in patients with ankylosing spondylitis (AS). (23rd January 2014) - Baraliakos, X.; Koenig, A.; Jones, H.; Szumski, A.; Collier, D.; Bananis, E.
Abstract : Background: A published report concluded AS patients with a disease duration (DisDur) <10 yrs had a better response to anti-TNF treatment than those with DisDur >10 yrs. [1] Objectives: To investigate the relationship between DisDur, baseline (BL) characteristics, and treatment responses in patients with AS. Methods: Data pooled from 4 clinical trials (placebo [PBO] or sulfasalazine [SSZ] versus etanercept [ETN]) were analyzed in 4 DisDur categories* and analyzed by age at diagnosis (≤40 or >40 yrs). Analyses conducted using Chi-Square tests and ANCOVA models. Results: 1281 patients analyzed; BL increasing age, decreasing age at diagnosis, and BL increasing BASFI significantly correlated with increasing DisDur categories (P<0.05). A higher % of patients responded to ETN compared to SSZ and PBO in all outcome measures and all DisDur categories. At Wk 12, patients with shorter DisDur had a tendency toward better response with ETN for most dichotomous outcomes, but not SSZ or PBO. This trend was significant for ETN when analyzing patients ≤40 yrs old at diagnosis. No significant differences were observed across DisDur for Wk 12 continuous outcomes (ASDAS, BASDAI, BASFI, etc.). Conclusions: Regardless of the time from diagnosis, and thus treatment initiation, ETN is more effective in patients with active AS compared to SSZ and PBO. Patients treated with ETN with DisDur ≤2 appeared to have the highest treatment response. Additional analyses are needed to further investigate the benefits of early treatment in AS. *DisDur categories analyzed as non-ordered, nominal using CMH test of general association and as ordered (trend) using CMH test of non-zero correlation. References: Rudwaleit et al. Ann Rheum Dis 2004;63:665–670. Disclosure of Interest: X. Baraliakos: None Declared, A. Koenig Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Jones Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Szumski Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Collier Shareholder of: Amgen Inc, Employee of: Amgen Inc, E. Bananis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc